Radiotherapy Quality Assurance for Head and Neck Squamous Cell Carcinoma - Van Gestel, Dirk; Dragan, Tatiana; Grégoire, Vincent; Evans, Mererid; Budach, Volker (Frontiers in Oncology, 2020)
The impact of quality assurance in radiotherapy was exemplarily evaluated from the results of numerous studies in head and neck cancer, which is a demanding subject due to the complexity of the tumor target and multiple organs at risk. The RT planning process in terms of the implementation of diagnostic imaging, image fusion and target volume definition including contouring of tumor, lymph nodes, and organs at risk has become highly complex and precise, that rigorous quality assurance for all the steps in the irradiation process is essential. The aim is putting exactly the right dose to the right place maximizing the tumor dose and thereby minimizing the dose to the organ at risk leading to an improved therapeutic index. Therefore, actual QA programs should systematically control all aspects of the treatment and include also regular end-to-end tests and external audits. However, comprehensive QA should not be limited to the radiotherapy, but also be implemented for surgery, medical oncology and other groups involved in the interdisciplinary treatment of HNC.